Multi band and Triple Notch band Tunable Monopole Circular Microstrip Antenna for Wireless Applications - Rajendra, Biradar; Mulgi, SN (International Journal of Computer Sciences and Engineering, 2020)
This paper presents a design and development of slot and stub loaded multi band and triple notch band tunable monopole circular microstrip antenna for different microwave communication applications. The antenna is loaded with U- slot, two identical I-slots and J-slot over the radiating patch .When the spacing between two identical I-slots is 0.21 and 0.11cm then the antenna tunes to the four required multi bands with three alternate notch bands. This tunable antenna is the replacement to the broadband antenna. The single antenna can be used to tune different microwave applications over a large range of frequencies. Thus, the antenna produces four useful bands with three alternate notch bands. The four useful bands tunes from 1.675-1.6525GHz, 2.53-2.71GHz, 5.095-5.4775GHz and 79075-7.0975GHz and three alternate notch bands tunes from 2.2375-2.3725GHz, 4.555-4.4875GHz and 5.7475-6.0625GHz respectively. These notch bands resolve the problem of crowding in the frequency spectrum and rejects Wi-Fi, UMTS, LTE, Wi-MAX, WLAN and C band frequencies. The maximum impedance bandwidth of proposed antennas for two spacing between identical I-slots is found to be 37.79 % and 48.33 % having peak gain of 2.14 dBi and 2.39 dBi respectively. The radiation patterns are omni directional in nature in both E and H plane.